Study of the growth activity of yeast and lactic acid bacteria on straw (Experimental biology, 2018)
Currently, due to the lack of feed for livestock, special attention is paid to microbial biomass as a source of protein. With the help of microorganisms, it is possible to obtain fodder protein and other protein-containing products, which contributes to reducing the protein deficit in feed. The production of such biomass on cheap raw materials is considered as one of the means of eliminating the growing protein deficiency in animal nutrition.In this regard, as the source of carbohydrates for the biosynthesis of fodder yeast, renewable plant raw materials are considered. As a plant raw material, agricultural crops and by-products and waste generated during processing are used. Such production facilities can provide an opportunity to obtain additional microbial protein for animal husbandry and, at the same time, to solve problems of utilization of waste polluting the environment.To increase the nutritional value of feeds, it is necessary to enrich the plant raw materials with a protein of microorganisms. Fortification of plant raw materials with a microbial protein is carried out by symbiosis of yeast and lactobacilli. Yeast, enriching the feed with protein and amino acids, creates the conditions for the development of lactobacilli, producers of biologically active animals beneficial.The activity of growth of yeast and lactic acid bacteria on agricultural wastes - wheat bran - has been studied. The protein accumulation activity and acid formation of yeast and lactic acid bacteria on an optimized medium were studied. As a result of the work, a consortium of yeasts and lactobacilli were designed for co-cultivation on plant substrates.Key words: fodder protein, consortium, yeast, lactic acid bacteria, biomass.